Examination of Exercise Addiction Levels of University Students - İhsan Kuyulu; Enes Beltekin (Türk Spor ve Egzersiz Dergisi)
The study was conducted to examine the addiction levels of university students. The research group consists of 343 male and 277 female totally 620 students in the academic year of 2019-2020 in Bingöl University School of Physical Education and Sports (Pesa), Faculty of Arts and Sciences and Vocational Schools. “Exercise Addiction Scale” was used to obtain data for the purpose of the research. The students participating in the study were asked personal information questions regarding their demographic characteristics. The study was carried out in SPSS 22 statistical package program and the degree of significance was taken as 0.05. Independent Sample T (Independent Sample) and Mann Whitney-U test in dual comparisons, One-Way Variance Analysis (One Way Anova) in multiple comparisons and Kruskal Wallis Analysis in non-normally distributed data, and correlation (Pearson) test to determine the relationship between variables. According to the answers given by the students who participated in the study, there was a significant difference between the groups in terms of gender, faculty, time spent on social media and academic grade point average. According to the results of the correlation analysis, a low level of meaningful relation was found between the time spent on social media and exercise addiction levels of the students.